Recursos didácticos para la asignatura de artes musicales énfasis en instrumentos de cuerda, y su incidencia en la profesionalización de la carrera de educación básica Universidad Técnica de Cotopaxi, extensión La Maná, año 2014 - Lovato Proaño, Wilson Mesias (2016)
The musical arts encompass important activities in education, allows you to acquire feelings, thoughts and emotions in such a way that facilitates the development of skills and attitudes in a spontaneous and natural way; however it has been found that in the students of the school "Dr. Nestor Mogollon Lopez" there is a deficit in terms to promote these musical activities that to more than be a relaxing activity promotes cultural values and traditions of national identity; this problem is due to various factors becoming somewhat alarming already seriously affecting in the learning and the integral development of the student.